Fiqh muasarah and E-Commerce: addressing ethical issues in online business transactions / Aida Khairani Zaidi … [et al.] - Zaidi, Aida Khairani; Mohd Sabri, Ainul Fatinah Dayini; Mahassan, Muthmainnah; Hashim, Rohani (2023)
In the past two decades, information technology has profoundly transformed global communication and the dissemination of knowledge. This shift is evident in the eagerness of certain Muslims to embrace technological progress, resulting in a surge of Islamic websites online. These websites serve diverse purposes, ranging from education and propagation of Islamic teachings to engaging in commercial or entertainment activities. Understanding the relationship between IT and Islam necessitates recognizing the Quran's universal principles, including those relevant to information technology. Implicitly, the Quran emphasizes the pursuit of knowledge, forging a direct link between IT and the acquisition of knowledge. Based on Surah Al-Mujadilah verse 11: